Cigarette Taxes and Cross-border Revenue Effects: Evidence Using Retail Data. (May 2016) - Nicholson, Andrew; Turner, Tracy M.; Alvarado, Eduardo
Episodes of large tax differentials between neighboring states create an incentive for cigarette tax avoidance by border crossing. We use unique quarterly panel data at the county level for the state of Kansas on cigarette retailers' sales tax remittances by distance to a state border to gauge the extent of smuggling activity and revenue effects of increases in cigarette excise tax rates. For quantities sold near an urban, low-tax border, we find sizable effects of higher excise tax rates on sales and cigarette excise tax revenues. Implications for cross-border state revenue leakages are discussed.